On modified Picard and Gauss—Weierstrass singular integrals - Rempulska, L.; Walczak, Z. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We introduce a certain modification of the Picard and Gauss—Weierstrass singular integrals and prove approximation theorems for them.